Threshold Concept for Promoting Business Transformation (Global Journal of Management and Business Research, 2023)
This qualitative study highlights the importance of considering the threshold concept for promoting the business transformation of large-sized enterprises The wide range of business literature and experts has debated how traditional large-sized companies can transform conventional approaches and mindset to be competitive For example many global enterprises now focus on digital transformation DX aiming to disrupt their conventional routines and adopt new DX knowledge and approaches The literature on leadership identifies how a business leader should behave for their staff to transform their conventional approach including promoting crisis awareness setting up a clear strategy vision and creating a DX department However without considering how to transform employees conventional way of thinking at the individual level a leader s action will be a unilateral announcement and the company cannot promote company-wide transformation
Keywords: threshold concept; leadership; business transformation; business knowledge